Role of Ultrasonography in The Differentiation of Solid Breast Mass (KYAMC Journal, 2021)
Background: Breast cancer is the major cause of cancer death in women. Breast ultrasound is of a great value in differentiating malignant from benign masses.Objective: To distinguish benign from malignant solid breast lesions by Ultrasonography (USG).Materials and Methods: This cross sectional study was performed in Radiology and Imaging department of Dhaka Community Medical College Hospital (DCMCH) in collaboration with the department of Pathology and Surgery, DCMCH from January 2017 to December 2017. The benign and malignant solid breast mass were differentiated by using USG and correlated these with histopathological findings.Results: Total 60 female with breast mass, aged 20 to 60 years, were studied. Out of 60 cases, 34 cases were solid breast mass on USG. Eleven cases were diagnosed as malignant and 23 cases as benign. Among the USG diagnosed 11 cases, 10 cases found truly malignant (true +ve) and 1 (one) case was benign (false+ve) whereas out of the 23 benign cases, 21 were benign (true -ve) and 2 (two) were found malignant(false-ve), and all were confirmed by histopathology.The sensitivity of USG for malignant breast mass was found 83.33% and specificity was 95.45%. The positive and negative predictive values of USG were 90.91% and 91.3% respectively. The diagnostic accuracy of USG in differentiating breast mass into malignant and benign was 91.318%.Conclusion: The USG is a very good diagnostic modality for differentiating benign and malignant breast mass.KYAMC Journal Vol. 11, No.-4, January 2021, Page 204-207